2009
DOI: 10.1159/000245930
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Adrenal Hyperplasia due to 11-Hydroxylase Deficiency – Insights from Two Novel <i>CYP11B1</i> Mutations (p.M92X, p.R453Q)

Abstract: Background: Steroid 11-hydroxylase (CYP11B1) deficiency (11OHD) is the second most common form of congenital adrenal hyperplasia (CAH). Herein, we describe two novel CYP11B1 mutations (g659_660dupTG, p.M92X; g.4817G>A, p.R453Q) found in a patient diagnosed with classic 11OHD, after presenting with borderline elevated 17-hydroxyprogesterone concentrations in CAH newborn screening. Methods: A novel CYP11B1 variant (p.R453Q) identified in a patient with classic 11OHD was characterized employing a COS7 cell assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
1
16
0
2
Order By: Relevance
“…This truncated protein contained 55 instead of 503 amino acid, lacking the very important domains, such as substrate recognitions sites, hemebinding sites and the putative steroid binding site [12,13]. So far, eight other nonsense mutations in CYP11B1 gene including p.Q19X [14], p.M92X [15], p.W116X [16], p.W247X [17], p.E265X [18], p.Q338X [11], p.Q356X [19] and p.Y423X [20] have been described. Like p.W56X, they all lacked the important functional domains and caused a classical 11-OHD.…”
Section: Discussionmentioning
confidence: 99%
“…This truncated protein contained 55 instead of 503 amino acid, lacking the very important domains, such as substrate recognitions sites, hemebinding sites and the putative steroid binding site [12,13]. So far, eight other nonsense mutations in CYP11B1 gene including p.Q19X [14], p.M92X [15], p.W116X [16], p.W247X [17], p.E265X [18], p.Q338X [11], p.Q356X [19] and p.Y423X [20] have been described. Like p.W56X, they all lacked the important functional domains and caused a classical 11-OHD.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in this domain most likely affect the binding between heme and C450. Several reported mutations, including p.R453Q, p.R448C, and p.R448H, have confirmed that this domain surrounding the C450 is very important in maintaining the activity of the enzyme (8,(14)(15)(16). Thus, the p.R454C mutant product may be associated with impairment of the binding between heme and C450.…”
Section: Figurementioning
confidence: 96%
“…Các đột biến P42S, N133H và T319M cũng làm suy giảm một phần hoạt tính 11β-hydroxylase (Joehrer et al, 1997). Krone và cộng sự Krone et al, 2009;Krone et al, 2007;Krone et al, 2005) đã phát hiện được các đột biến mới W116C, L299P, DeltaF438, P94L. Đột biến A368D làm giảm 1,17% hoạt tính của 11-deoxycortisol , đột biến R43Q làm hoạt tính 11-hydroxylase giảm từ 30-50% (Barr et al, 2006), đột biến L22P giảm 1,6% hoạt tính enzyme… Ngoài ra, khi kết hợp phân tích chức năng enzyme bằng tạo đột biến điểm trực tiếp và cấu trúc không gian sẽ cho chúng ta có hiểu biết sâu về mối quan hệ giữa cấu trúc và chức năng của enzyme (Bảng 2).…”
Section: Tình Hình Nghiên Cứu Bệnh Thiếu Hụt 11β-hydroxylaseunclassified
“…Tại Việt Nam đã có một số nghiên cứu phát hiện đột biến trên gen CYP11B1 và phân tích sự ảnh hưởng của các đột biến mới. Nguyễn Huy Hoàng và các đồng tác giả (Nguyen et al, 2012) (Krone et al, 2009) A368D 6 K-helix 1,17% North German L299P 5 I-helix 1,2% Iraq (Krone et al, 2005) A331V 6 I-helix 0% Caucasian (Geley et al, 1996) E371G 6 K-helix 0% Caucasian (Geley et al, 1996) R384G 7 Heme propionate neutralisation 0% Nhật bản (Yang et al, 1995) T318M 5 I-helix 0% Yemenite (Curnow et al, 1993) R374Q 6 K-helix 0% Lebanese Arab (Curnow et al, 1993) V441G 8 Meander 0% White (Curnow et al, 1993) Ngày nay, với các tiến bộ của sinh học phân tử, các nhà khoa học đã ứng dụng các kỹ thuật tiên tiến như giải trình tự gen, MLPA… (Menabo et al, 2015;Nguyen et al, 2015) để phát hiện các đột biến trên gen CYP11B1. Các đột biến trên gen CYP11B1 được tìm thấy rất đa dạng và rải rác trên toàn bộ gen (Hình 2).…”
Section: Tình Hình Nghiên Cứu Bệnh Thiếu Hụt 11β-hydroxylaseunclassified